Mortality by country of birth in the Nordic countries – a systematic review of the literature - Honkaniemi, Helena; Bacchus-Hertzman, Jennie; Fritzell, Johan; Rostila, Mikael (BMC Public Health, 2017)
Immigration to the Nordic countries has increased in the last decades and foreign-born inhabitants now constitute a considerable part of the region’s population. Several studies suggest poorer self-reported health among foreign-born compared to natives, while results on mortality and life expectancy are inconclusive. To date, few studies have summarized knowledge on mortality differentials by country of birth. This article aims to systematically review previous results on all-cause and cause-specific mortality by country of birth in the Nordic countries.